Risk of persistent or recurrent neoplasia in conservatively treated women with cervical adenocarcinoma in situ with negative histological margins. (6th March 2017) - Munro, Aime; Codde, Jim; Spilsbury, Katrina; Stewart, Colin J.R.; Steel, Nerida; Leung, Yee; Tan, Jason; Salfinger, Stuart G.; Mohan, Ganendra R.; Semmens, James B.; Cohen, Paul A.
Abstract: Introduction: Conservative treatments including cold knife cone biopsy (CKC) or loop electrosurgical excision procedure (LEEP) are fertility‐preserving alternatives to hysterectomy. The risks of persistent cervical neoplasia in women with negative surgical margins following conservative treatment of adenocarcinoma‐in‐situ (AIS) are uncertain. This study aims to investigate the risk of persistent or recurrent cervical neoplasia [AIS, adenocarcinoma and/or high‐grade cervical squamous intraepithelial neoplasia (CIN)] and compliance with follow‐up recommendations in conservatively treated women with AIS and negative histopathological margins. Material and methods: A retrospective, population‐based study of Western Australian women treated by CKC or LEEP for AIS between 2001 and 2012. Histopathology reports were reviewed for demographic information, treatment procedures and clinicopathological factors. Primary outcomes were the diagnosis of cervical neoplasia during follow‐up (defined as <12 months) and surveillance (≥12 months) periods. Results: The cohort comprised 360 women, with 175 (48.6%) initially treated by CKC and 185 (51.4%) treated by LEEP. The median patient age at time of excisional treatment was 30.0 years (range 18–64 years) and the median follow‐up time was 3.9 years (range six months to 12.2 years). During the follow‐up and surveillance periods, seven (1.9%) women were diagnosed with CIN 2/3, 10 (2.8%) with AIS, and one (0.3%) with cervical adenocarcinoma, despite their initial excision specimens having negative histological margins. Conclusion: In this study, there was a low but significant risk of persistent or recurrent cervical neoplasia in women who had initial conservative management of AIS with negative histopathological margins.